Compositional dependency on dissolution rate and cytocompatibility of phosphate-based glasses: effect of B2O3 and Fe2O3 addition - Sharmin, Nusrat; Gu, Fu; Ahmed, Ifty; Parsons, Andrew J (SAGE, 2017)
The unique property of phosphate-based glasses and fibres to be completely dissolved in aqueous media is largely dependent on the glass composition. This article focuses on investigating the effect of replacing Na2O with 3 and 5 mol% Fe2O3 on cytocompatibility, thermal and dissolution properties of P2O5–CaO–Na2O–MgO–B2O3 glass system, where P2O5 content was fixed at 45 mol%. The effect of increasing Fe2O3 from 3 to 5 mol% on P2O5–CaO–Na2O–MgO glasses was also evaluated. The glass transition temperature, onset of crystallisation temperature and liquidus temperature were found to decrease with increasing Fe2O3 content and the addition of B2O3, while the thermal expansion values were found to decrease. The density of the glasses decreased with increasing Fe2O3 content. However, an increase in the density was observed by the addition of 5 mol% B2O3. The dissolution properties and mode of bulk glass and fibres were also examined which were found to decrease with increasing B2O3 and Fe2O3. However, it was found that the dissolution properties of the glasses containing both B2O3 and Fe2O3 were lower than only Fe2O3 containing glasses. The in vitro cell culture studies using human osteoblast like (MG63) cell lines revealed that the glasses containing both B2O3 and Fe2O3 maintained and showed higher cell viability as compared to the only Fe2O3 containing glasses. Glasses containing both B2O3 and Fe2O3 showed a pronounced effect on the dissolution rate of the glasses, which eventually improved the cytocompatibility properties of the glasses investigated.